Analysis of university graduates’ competencies for the position of internal auditors: Perspective of internal auditor practitioners - Hansiadi Yuli Hartanto; Lisia Apriani (Journal of Economics, Business, and Accountancy Ventura, 2014)
This study aims to determine what competencies are required when recruiting internal auditors. It is expected that the results of this study can be used as a guide for developing accounting curriculum related to internal audit. Beside, it can be used to design training to further sharpen internal audit skills in preparing students to enter the internal audit position. The study involved 99 practitioners of internal auditors of various companies’ types in Indonesia. This study used a Likert scale to measure the  competencies considered by the internal audit manager in recruiting university graduates. Each statement is analyzed on the distribution of respondents by counting the frequency of respondents' answers. It shows that there are seven essential factors that must be considered when hiring internal auditors. They are the core curriculum which must include mastery of the material consist of ethics and corporate governance, information technology, internal audit, and business communications; factors associated with student activities such as the ability to work individually and in teams, the using of information technology to complete the task, and the analyzing accounting problem comprehensively. All factors associated with the certification of students are essential in recruiting internal auditor.